Ultra-thin thermal conductive tape and preparation method thereof
By adopting a combination design of a thermal adhesive layer and a release film of a specific formula, ultra-thin thermal tape with excellent thermal conductivity, high temperature resistance and bonding performance was prepared, which solved the problems of insufficient thermal conductivity, limited bonding performance and insufficient high temperature resistance in the prior art, and met the demand for heat dissipation in the thin and thin design of electronic devices.
Patent Information
- Application Number
- CN202310915524.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-07-25
AI Technical Summary
The existing ultra-thin thermal tape has shortcomings in thermal conductivity, bonding performance and high temperature resistance, and it is difficult to meet the needs of lightweight and thin design of electronic devices for heat dissipation.
A thermally conductive adhesive layer made of polyethersulfone type hyperbranched epoxy resin with end groups as epoxy groups, soluble rosin-based polyimide, nanoboron fibers and thermal fillers (graphene, diamond, boron nitride, silicon carbide) and other materials was prepared by thermal pressing and maturation. Combined with the design of the release film, ultra-thin thermal tape with excellent thermal conductivity, high temperature resistance and bonding properties were prepared.
It has achieved improvements in thermal conductivity, improved high temperature resistance and bonding performance, extended service life, and is suitable for heat dissipation applications of electronic devices.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic adhesive products, and in particular to an ultra-thin thermal conductive tape and a preparation method thereof. Background Art
[0002] The development of science and technology and market demand have led electronic devices to develop in the direction of miniaturization, lightness, compact structure and high efficiency. The working efficiency and working intensity of thin and light electronic devices are increasing, and the internal power density is significantly increased, which makes it difficult to dissipate heat well during operation, thereby reducing the usability and reliability of electronic equipment. It can be seen that the heat dissipation effect is the key to the thin and light design of electronic devices.
[0003] In order to achieve fast and efficient heat dissipation, thermal conductive tape is indispensable. In electronic equipment, various heat source generators and heat sinks are connected by thermal conductive tape. Thermal conductive tape is not only used to fix components on circuit boards, but also can conduct and dissipate the large amount of heat generated inside electronic components in a timely manner. The performance of thermal conductive tape directly affects the heat dissipation effect. Developing thermal conductive tape with excellent comprehensive performance and performance stability is the key to ensuring the normal operation of electronic components, extending service life, and improving the safety and reliability of electronic equipment.
[0004] Ultra-thin thermal conductive tape can make full use of the compact internal space of electronic products and is conducive to heat dissipation. It is a kind of tape developed to meet the requirements of the development of thin and light electronic devices. However, the ultra-thin thermal conductive tapes on the market still have more or less defects such as poor thermal conductivity, limited bonding performance, and high temperature resistance performance needs to be further improved.
[0005] In order to solve the above defects, Chinese patent document CN104178048B discloses an ultra-thin thermally conductive tape, wherein the tape is a single-sided tape or a double-sided tape with a substrate or without a substrate; when the tape is a tape without a substrate, the tape is composed of a thermally conductive adhesive with a thickness of 0.5-2μm; when the tape is a tape with a substrate, the tape is composed of a substrate with a thickness of 1-5μm and a single-sided or double-sided total thickness of 0.5-2μm. The thermally conductive adhesive is made of a polymer polymer with nano-ceramic thermal conductive fillers, nano-metal thermal conductive fillers, and carbon nanotubes or graphene added. The ultra-thin thermally conductive tape of the invention can be made as thin as 0.5μm and has a thermal conductivity of more than 20W / (m·k) due to the use of the above-mentioned thermally conductive adhesive, and the thermally conductive tape at this thickness can have greater mechanical strength and better mechanical properties than the existing thermally conductive tape. However, the high temperature resistance and bonding properties of the thermally conductive tape need to be further improved.
[0006] It can be seen that the development of an ultra-thin thermally conductive tape with good thermal conductivity, high temperature resistance and bonding properties, and long service life and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the ultra-thin thermally conductive tape field. Summary of the invention
[0007] The main purpose of the present invention is to provide an ultra-thin thermal conductive tape with good thermal conductivity, high temperature resistance and bonding performance, and long service life, and a preparation method thereof.
[0008] To achieve the above purpose, the present invention provides an ultra-thin thermally conductive adhesive tape, which comprises a first release layer, a thermally conductive adhesive layer and a second release layer in order from top to bottom; the thermally conductive adhesive layer comprises the following raw materials in parts by weight: 20-30 parts of polyethersulfone type hyperbranched epoxy resin with epoxy end groups, 8-12 parts of soluble rosin-based polyimide, 2-4 parts of 4,4-diaminodiphenyl sulfide, 1-3 parts of benzoguanamine, 1-3 parts of glycidyl ether oxypropyl cage-type polysilsesquioxane, 3-5 parts of nano-boron fiber, 1-3 parts of coupling agent, 35-45 parts of thermally conductive filler, and 70-100 parts of solvent.
[0009] Preferably, there is no special requirement for the source of the polyethersulfone type hyperbranched epoxy resin with epoxy terminal groups. In one embodiment of the present invention, the polyethersulfone type hyperbranched epoxy resin with epoxy terminal groups is prepared according to the method in Implementation Case 18 in Chinese invention patent document CN104311832B.
[0010] Preferably, there is no special requirement for the source of the soluble rosin-based polyimide. In one embodiment of the present invention, the soluble rosin-based polyimide is prepared according to the method in Example 1 in Chinese invention patent document CN102690414B.
[0011] Preferably, the CAS number of the glycidyl ether oxypropyl cage-type polysilsesquioxane is 164017-77-0, and the model is Ecotion®POSS101.
[0012] Preferably, the average diameter of the nano-boron fiber is 100-300 nm and the length is 3-6 mm.
[0013] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
[0014] Preferably, the thermally conductive filler is a mixture of graphene, diamond, boron nitride and silicon carbide in a mass ratio of 1:(0.8-1.2):(0.5-0.8):(0.3-0.5).
[0015] Preferably, the graphene is a single-layer graphene powder with a flake diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm.
[0016] Preferably, the particle size of the diamond is 1000-1300 mesh, the particle size of the boron nitride is 800-1000 mesh, and the particle size of the silicon carbide is 500-800 mesh.
[0017] Preferably, the solvent is any one of N-methylpyrrolidone and N,N-dimethylformamide.
[0018] Preferably, the thickness of the first release layer is 20-30 microns, the thickness of the second release layer is 20-30 microns; and the thickness of the thermal conductive adhesive layer is 0.5-2 microns.
[0019] Preferably, the first release layer is made of any one of a PET release film, a CPP film, an OPP film, a BOPP film, and a release paper.
[0020] Preferably, the second release layer is made of any one of a PET release film, a CPP film, an OPP film, a BOPP film, and a release paper.
[0021] Another object of the present invention is to provide a method for preparing an ultra-thin thermally conductive tape, comprising the following steps:
[0022] Step S1, mixing the raw materials of the thermal conductive adhesive layer according to weight and stirring evenly;
[0023] Step S2, coating on the first release layer to form a thermal conductive adhesive layer; and then laminating the thermal conductive adhesive layer with the second release layer. After rolling up, the thermal conductive adhesive tape is placed at 30-50° C. for aging for 3-5 days to obtain an ultra-thin thermal conductive adhesive tape.
[0024] Preferably, the coating speed in step S2 is 8-18 m / min.
[0025] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0026] (1) The ultra-thin thermally conductive tape disclosed in the present invention can conduct heat more quickly due to the ultra-thin and substrate-free design of the tape, which is beneficial to the heat dissipation of electronic components. It can be directly bonded with a release film, has a simple preparation process, is easy to operate and use, has high preparation efficiency and finished product qualification rate, has low dependence on equipment, is suitable for continuous large-scale production, and has high promotion and application value.
[0027] (2) The ultra-thin thermally conductive tape disclosed in the present invention comprises a thermally conductive filler which is a mixture of graphene, diamond, boron nitride and silicon carbide in a mass ratio of 1:(0.8-1.2):(0.5-0.8):(0.3-0.5); by compounding these thermally conductive filler components and their particle sizes, the thermal conductivity and heat dissipation capacity of the tape are improved while maintaining the adhesive performance of the tape.
[0028] (3) The ultra-thin thermally conductive adhesive tape disclosed in the present invention, wherein the thermally conductive adhesive layer comprises the following raw materials in parts by weight: 20-30 parts of polyethersulfone type hyperbranched epoxy resin with epoxy end groups, 8-12 parts of soluble rosin-based polyimide, 2-4 parts of 4,4-diaminodiphenyl sulfide, 1-3 parts of benzoguanamine, 1-3 parts of glycidyl ether oxypropyl cage-type polysilsesquioxane, 3-5 parts of nano-boron fiber, 1-3 parts of coupling agent, 35-45 parts of thermally conductive filler, and 70-100 parts of solvent. Through the mutual cooperation between the raw materials, the ultra-thin thermally conductive adhesive tape has good thermal conductivity, high temperature resistance and bonding performance, and long service life. In the molecular structure of the thermal conductive adhesive layer, polyethersulfone hyperbranched epoxy resin, rosin-based polyimide, phenylene sulfide, benzoguanamine and cage-type polysilsesquioxane structures are simultaneously introduced. Under the multiple effects of electronic effect, steric effect and conjugation effect, these structures further improve the thermal conductivity, high temperature resistance and bonding performance of the tape, and further extend the service life. By compounding with nano-boron fiber, the mechanical properties and thermal conductivity and heat dissipation performance are further improved. DETAILED DESCRIPTION
[0029] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0030] An ultra-thin thermally conductive tape comprises, from top to bottom, a first release layer, a thermally conductive adhesive layer and a second release layer; the thermally conductive adhesive layer comprises the following raw materials in parts by weight: 20 parts of polyethersulfone type hyperbranched epoxy resin with epoxy end groups, 8 parts of soluble rosin-based polyimide, 2 parts of 4,4-diaminodiphenyl sulfide, 1 part of benzoguanamine, 1 part of glycidyl ether oxypropyl cage-type polysilsesquioxane, 3 parts of nano-boron fiber, 1 part of coupling agent, 35 parts of thermally conductive filler and 70 parts of solvent.
[0031] The polyethersulfone type hyperbranched epoxy resin with epoxy end groups is prepared according to the method in Example 18 in Chinese invention patent document CN104311832B; the soluble rosin-based polyimide is prepared according to the method in Example 1 in Chinese invention patent document CN102690414B; the CAS number of the glycidyl ether oxypropyl cage-type polysilsesquioxane is 164017-77-0, and the model is Ecotion®POSS101; the average diameter of the nano-boron fiber is 100nm and the length is 3mm.
[0032] The coupling agent is silane coupling agent KH550; the thermal conductive filler is a mixture of graphene, diamond, boron nitride and silicon carbide in a mass ratio of 1:0.8:0.5:0.3; the graphene is a single-layer graphene powder with a sheet diameter of 0.5 μm and a thickness of 0.8 nm; the particle size of the diamond is 1000 mesh, the particle size of the boron nitride is 800 mesh, and the particle size of the silicon carbide is 500 mesh; and the solvent is N-methylpyrrolidone.
[0033] The thickness of the first release layer is 20 microns, and the thickness of the second release layer is 20 microns; the thickness of the thermal conductive adhesive layer is 1 micron; the preparation material of the first release layer is PET release film; the preparation material of the second release layer is PET release film.
[0034] A method for preparing an ultra-thin thermally conductive tape comprises the following steps:
[0035] Step S1, mixing the raw materials of the thermal conductive adhesive layer according to weight and stirring evenly;
[0036] Step S2, coating on the first release layer to form a thermal conductive adhesive layer; then laminating the thermal conductive adhesive layer with the second release layer, and after rolling up, curing at 30°C for 3 days to obtain an ultra-thin thermal conductive tape; the coating speed in step S2 is 8m / min. Example 2
[0037] An ultra-thin thermally conductive adhesive tape comprises, from top to bottom, a first release layer, a thermally conductive adhesive layer and a second release layer; the thermally conductive adhesive layer comprises the following raw materials in parts by weight: 23 parts of polyethersulfone type hyperbranched epoxy resin with epoxy end groups, 9 parts of soluble rosin-based polyimide, 2.5 parts of 4,4-diaminodiphenyl sulfide, 1.5 parts of benzoguanamine, 1.5 parts of glycidyl ether oxypropyl cage-type polysilsesquioxane, 3.5 parts of nano-boron fiber, 1.5 parts of coupling agent, 37 parts of thermally conductive filler and 80 parts of solvent.
[0038] The polyethersulfone type hyperbranched epoxy resin with epoxy end groups is prepared according to the method in Example 18 in Chinese invention patent document CN104311832B; the soluble rosin-based polyimide is prepared according to the method in Example 1 in Chinese invention patent document CN102690414B; the CAS number of the glycidyl ether oxypropyl cage-type polysilsesquioxane is 164017-77-0, and the model is Ecotion®POSS101.
[0039] The average diameter of the nano-boron fiber is 150nm and the length is 4mm; the coupling agent is silane coupling agent KH560; the thermal conductive filler is a mixture of graphene, diamond, boron nitride and silicon carbide in a mass ratio of 1:0.9:0.6:0.35; the graphene is a single-layer graphene powder with a sheet diameter of 2μm and a thickness of 0.9nm; the particle size of the diamond is 1100 mesh, the particle size of the boron nitride is 850 mesh, and the particle size of the silicon carbide is 600 mesh; and the solvent is N,N-dimethylformamide.
[0040] The thickness of the first release layer is 23 microns, and the thickness of the second release layer is 22 microns; the thickness of the thermal conductive adhesive layer is 1 micron; the preparation material of the first release layer is CPP film; the preparation material of the second release layer is CPP film.
[0041] A method for preparing an ultra-thin thermally conductive tape comprises the following steps:
[0042] Step S1, mixing the raw materials of the thermal conductive adhesive layer according to weight and stirring evenly;
[0043] Step S2, coating on the first release layer to form a thermal conductive adhesive layer; then laminating the thermal conductive adhesive layer with the second release layer, and after rolling up, placing it at 35°C for aging for 3.5 days to obtain an ultra-thin thermal conductive tape; the coating speed in step S2 is 11m / min. Example 3
[0044] An ultra-thin thermally conductive adhesive tape comprises, from top to bottom, a first release layer, a thermally conductive adhesive layer and a second release layer; the thermally conductive adhesive layer comprises the following raw materials in parts by weight: 25 parts of polyethersulfone type hyperbranched epoxy resin with epoxy end groups, 10 parts of soluble rosin-based polyimide, 3 parts of 4,4-diaminodiphenyl sulfide, 2 parts of benzoguanamine, 2 parts of glycidyl ether oxypropyl cage-type polysilsesquioxane, 4 parts of nano-boron fiber, 2 parts of coupling agent, 40 parts of thermally conductive filler and 85 parts of solvent.
[0045] The polyethersulfone type hyperbranched epoxy resin with epoxy end groups is prepared according to the method in Example 18 in Chinese invention patent document CN104311832B; the soluble rosin-based polyimide is prepared according to the method in Example 1 in Chinese invention patent document CN102690414B; the CAS number of the glycidyl ether oxypropyl cage-type polysilsesquioxane is 164017-77-0, and the model is Ecotion®POSS101.
[0046] The average diameter of the nano-boron fiber is 200nm and the length is 4.5mm; the coupling agent is silane coupling agent KH570; the thermal conductive filler is a mixture of graphene, diamond, boron nitride and silicon carbide in a mass ratio of 1:1:0.65:0.4; the graphene is a single-layer graphene powder with a sheet diameter of 3.5μm and a thickness of 1nm; the particle size of the diamond is 1150 mesh, the particle size of the boron nitride is 900 mesh, and the particle size of the silicon carbide is 650 mesh; the solvent is N-methylpyrrolidone.
[0047] The thickness of the first release layer is 25 microns, and the thickness of the second release layer is 25 microns; the thickness of the thermal conductive adhesive layer is 1 micron; the preparation material of the first release layer is OPP film; the preparation material of the second release layer is OPP film.
[0048] A method for preparing an ultra-thin thermally conductive tape comprises the following steps:
[0049] Step S1, mixing the raw materials of the thermal conductive adhesive layer according to weight and stirring evenly;
[0050] Step S2, coating on the first release layer to form a thermal conductive adhesive layer; then laminating the thermal conductive adhesive layer with the second release layer, and after rolling up, placing it at 40°C for aging for 4 days to obtain an ultra-thin thermal conductive tape; the coating speed in step S2 is 14m / min. Example 4
[0051] An ultra-thin thermally conductive adhesive tape comprises, from top to bottom, a first release layer, a thermally conductive adhesive layer and a second release layer; the thermally conductive adhesive layer comprises the following raw materials in parts by weight: 28 parts of polyethersulfone type hyperbranched epoxy resin with epoxy end groups, 11 parts of soluble rosin-based polyimide, 3.5 parts of 4,4-diaminodiphenyl sulfide, 2.5 parts of benzoguanamine, 2.5 parts of glycidyl ether oxypropyl cage-type polysilsesquioxane, 4.5 parts of nano-boron fiber, 2.5 parts of coupling agent, 43 parts of thermally conductive filler and 95 parts of solvent.
[0052] The polyethersulfone type hyperbranched epoxy resin with epoxy end groups is prepared according to the method in Example 18 in Chinese invention patent document CN104311832B; the soluble rosin-based polyimide is prepared according to the method in Example 1 in Chinese invention patent document CN102690414B; the CAS number of the glycidyl ether oxypropyl cage-type polysilsesquioxane is 164017-77-0, and the model is Ecotion®POSS101.
[0053] The average diameter of the nano-boron fiber is 250nm and the length is 5.5mm; the coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570 in a mass ratio of 1:1:3; the thermal conductive filler is a mixture of graphene, diamond, boron nitride and silicon carbide in a mass ratio of 1:1:0.65:0.45; the graphene is a single-layer graphene powder with a sheet diameter of 4.5μm and a thickness of 1.1nm; the particle size of the diamond is 1250 mesh, the particle size of the boron nitride is 950 mesh, and the particle size of the silicon carbide is 750 mesh; the solvent is a mixture of N-methylpyrrolidone and N,N-dimethylformamide in a mass ratio of 3:5.
[0054] The thickness of the first release layer is 28 microns, and the thickness of the second release layer is 28 microns; the thickness of the thermal conductive adhesive layer is 1 micron; the preparation material of the first release layer is OPP film; the preparation material of the second release layer is OPP film.
[0055] A method for preparing an ultra-thin thermally conductive tape comprises the following steps:
[0056] Step S1, mixing the raw materials of the thermal conductive adhesive layer according to weight and stirring evenly;
[0057] Step S2, coating on the first release layer to form a thermal conductive adhesive layer; then laminating the thermal conductive adhesive layer with the second release layer, and after rolling up, placing it at 45°C for aging for 4.5 days to obtain an ultra-thin thermal conductive tape; the coating speed in step S2 is 16m / min. Example 5
[0058] An ultra-thin thermally conductive tape comprises, from top to bottom, a first release layer, a thermally conductive adhesive layer and a second release layer; the thermally conductive adhesive layer comprises the following raw materials in parts by weight: 30 parts of polyethersulfone type hyperbranched epoxy resin with epoxy end groups, 12 parts of soluble rosin-based polyimide, 4 parts of 4,4-diaminodiphenyl sulfide, 3 parts of benzoguanamine, 3 parts of glycidyl ether oxypropyl cage-type polysilsesquioxane, 5 parts of nano-boron fiber, 3 parts of coupling agent, 45 parts of thermally conductive filler and 100 parts of solvent.
[0059] The polyethersulfone type hyperbranched epoxy resin with epoxy end groups is prepared according to the method in Example 18 in Chinese invention patent document CN104311832B; the soluble rosin-based polyimide is prepared according to the method in Example 1 in Chinese invention patent document CN102690414B; the CAS number of the glycidyl ether oxypropyl cage-type polysilsesquioxane is 164017-77-0, and the model is Ecotion®POSS101.
[0060] The average diameter of the nano-boron fiber is 300nm and the length is 6mm; the coupling agent is silane coupling agent KH550; the thermal conductive filler is a mixture of graphene, diamond, boron nitride and silicon carbide in a mass ratio of 1:1.2:0.8:0.5; the graphene is a single-layer graphene powder with a sheet diameter of 5μm and a thickness of 1.2nm; the particle size of the diamond is 1300 mesh, the particle size of the boron nitride is 1000 mesh, and the particle size of the silicon carbide is 800 mesh; and the solvent is N-methylpyrrolidone.
[0061] The thickness of the first release layer is 30 microns, and the thickness of the second release layer is 30 microns; the thickness of the thermal conductive adhesive layer is 1 micron; the preparation material of the first release layer is BOPP film; the preparation material of the second release layer is BOPP film.
[0062] A method for preparing an ultra-thin thermally conductive tape comprises the following steps:
[0063] Step S1, mixing the raw materials of the thermal conductive adhesive layer according to weight and stirring evenly;
[0064] Step S2, coating on the first release layer to form a thermal conductive adhesive layer; then laminating the thermal conductive adhesive layer with the second release layer, and after rolling up, placing it at 50°C for aging for 5 days to obtain an ultra-thin thermal conductive tape; the coating speed in step S2 is 18m / min.
[0065] Comparative Example 1
[0066] The present invention provides an ultra-thin thermally conductive tape, which is similar to Example 1, except that no soluble rosin-based polyimide and graphene are added.
[0067] Comparative Example 2
[0068] The present invention provides an ultra-thin thermally conductive tape, which is similar to Example 1, except that benzoguanamine, nano-boron fiber and diamond are not added.
[0069] In order to further illustrate the unexpected beneficial technical effects of the ultra-thin thermally conductive tape involved in the embodiments of the present application, relevant performance tests were carried out on the ultra-thin thermally conductive tapes prepared in each group of Examples 1-5 and Comparative Examples 1-2. The test reference standards and test results are shown in Table 1; the high temperature resistance performance is measured by placing the tape at 120°C for 10 hours and then observing whether there is loosening or cracking. If there is no loosening or cracking, the high temperature resistance performance is qualified, otherwise it is unqualified.
[0070]
[0071] It can be seen from Table 1 that the ultra-thin thermally conductive tape prepared in the embodiment of the present invention has better peel strength, initial adhesion and high temperature resistance, and better thermal conductivity. The addition of soluble rosin-based polyimide, graphene, benzoguanamine, nano-boron fiber and diamond is beneficial to improving the above properties.
[0072] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. An ultra-thin thermally conductive tape, characterized in that: The invention comprises, from top to bottom, a first release layer, a thermally conductive adhesive layer and a second release layer; the thermally conductive adhesive layer comprises the following raw materials in parts by weight: 20-30 parts of polyethersulfone hyperbranched epoxy resin with epoxy end groups, 8-12 parts of soluble rosin-based polyimide, 2-4 parts of 4,4-diaminodiphenyl sulfide, 1-3 parts of benzoguanamine, 1-3 parts of glycidyloxypropyl cage-type polysilsesquioxane, 3-5 parts of nano-boron fiber, 1-3 parts of coupling agent, 35-45 parts of thermally conductive filler and 70-100 parts of solvent; the thermally conductive filler is a mixture formed by mixing graphene, diamond, boron nitride and silicon carbide in a mass ratio of 1:(0.8-1.2):(0.5-0.8):(0.3-0.5).
2. The ultra-thin thermally conductive tape according to claim 1, characterized in that: The model of the glycidyl ether oxygen propyl cage-type polysilsesquioxane is Ecotion®POSS101.
3. The ultra-thin thermally conductive tape according to claim 1, characterized in that: The average diameter of the nano boron fiber is 100-300nm, and the length is 3-6mm.
4. The ultra-thin thermally conductive tape according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.
5. The ultra-thin thermally conductive tape according to claim 1, characterized in that: The graphene is a single-layer graphene powder with a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm; the particle size of the diamond is 1000-1300 meshes, the particle size of the boron nitride is 800-1000 meshes, and the particle size of the silicon carbide is 500-800 meshes.
6. The ultra-thin thermally conductive tape according to claim 1, characterized in that: The solvent is any one of N-methylpyrrolidone and N,N-dimethylformamide.
7. The ultra-thin thermally conductive tape according to claim 1, characterized in that: The thickness of the first release layer is 20-30 microns, and the thickness of the second release layer is 20-30 microns; the thickness of the thermal conductive adhesive layer is 0.5-2 microns; the preparation material of the first release layer is any one of PET release film, CPP film, OPP film, BOPP film, and release paper; the preparation material of the second release layer is any one of PET release film, CPP film, OPP film, BOPP film, and release paper.
8. A method for preparing the ultra-thin thermally conductive tape according to any one of claims 1 to 7, characterized in that: The steps include: Step S1, mixing the raw materials of the thermal conductive adhesive layer according to weight and stirring evenly; Step S2, coating on the first release layer to form a thermal conductive adhesive layer; and then laminating the thermal conductive adhesive layer with the second release layer. After rolling up, the thermal conductive adhesive tape is placed at 30-50° C. for aging for 3-5 days to obtain an ultra-thin thermal conductive adhesive tape.
9. The method for preparing the ultra-thin thermally conductive tape according to claim 8, characterized in that: The coating speed in step S2 is 8-18 m / min.
Citation Information
Patent Citations
Soluble rosinyl polyimide, film and preparation method of film
CN102690414B
An ultra-thin thermally conductive tape
CN104178048B
Preparation method of a polyethersulfone-based hyperbranched epoxy resin and its application in toughening linear epoxy resin
CN104311832B
Soluble rosinyl polyimide, film and preparation method of film
CN102690414A
Directional high-heat-conductivity ultrathin single-side adhesive tape and double-side adhesive tape
CN109880542A